2020
DOI: 10.1021/acs.jced.0c00878
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Pressures and Thermophysical Properties of 1-Heptanol, 1-Octanol, 1-Nonanol, and 1-Decanol: Data Reconciliation and PC-SAFT Modeling

Abstract: were measured by a static method near ambient temperatures over an operating pressure range from 0.5 to 1270 Pa, thus complementing literature vapor pressure data obtained by ebulliometry at higher temperatures. Liquid heat capacities of 1-octanol, 1-nonanol, and 1decanol were determined by Tian−Calvet calorimetry. Ideal-gas thermodynamic properties of 1-alkanols up to 1-heptanol were obtained by a combination of quantum chemistry and statistical mechanics and validated against available experimental data. Ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 75 publications
0
24
0
Order By: Relevance
“…1-Octanol (CAS 111-987-5; M = 0.13023 kg/mol; ρ­(298 K) = 830 kg/m 3 ) has a vapor pressure of 11.18 Pa at 298 K . The solubility of water in 1-octanol at 298 K is 48.79 mg/g (mole fraction 0.2701) (see Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…1-Octanol (CAS 111-987-5; M = 0.13023 kg/mol; ρ­(298 K) = 830 kg/m 3 ) has a vapor pressure of 11.18 Pa at 298 K . The solubility of water in 1-octanol at 298 K is 48.79 mg/g (mole fraction 0.2701) (see Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…A modification of the approach denoted R1TM was introduced, where all terminal tops (thus letter “T” in the acronym) are treated using the 1-D HR model instead of only symmetrical tops as in the original R1SM approach. Use of the R1TM approach significantly improved the agreement with experimental ideal-gas data for n -alkanols …”
Section: Resultsmentioning
confidence: 88%
“…It combines carefully selected quantum chemistry calculations and three statistical mechanics models: (i) the rigid rotor–harmonic oscillator (RRHO) approximation; (ii) corrections for symmetric top rotations using the one-dimensional hindered rotor approximation (1-DHR); (iii) mixing model using the population of conformers based on the Boltzmann distribution. We recently revealed that treating the hydroxyl groups with their low rotational barriers by combination of HO and mixing model, as suggested in the R1SM approach, is inadequate . A modification of the approach denoted R1TM was introduced, where all terminal tops (thus letter “T” in the acronym) are treated using the 1-D HR model instead of only symmetrical tops as in the original R1SM approach.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations